Analisis Penerapan Pembelajaran Berdiferensiasi Dalam Implementasi Kurikulum Merdeka Pada Pembelajaran Matematika Di SD Negeri 1 Imbanagara Raya - Nunung Nurjanah; Syamsudin Syamsudin (JURNAL MANAJEMEN PENDIDIKAN, 2023)
ANALYSIS OF DEEP DIFFERENTIATE LEARNING APPLICATION IMPLEMENTATION OF INDEPENDENT CURRICULUM IN MATHEMATICS LEARNING AT SDN 1 IMBANAGARA RAYAThe current mathematics curriculum is basically (in many countries) aligned with the expectations outlined in the United States of America National Council of Teachers of Mathematics Standards curriculum, which is a very influential organization of the mathematics education profession in the United States, which since the 1980s has called for a complete overhaul of the practice of learning mathematics in many countries, including in the United States itself, which among other things encourages the method of learning mathematics to shift from teacher-centered Learning to student-centered Learning and change students who previously are passive learners (passive learners) become students are active learners (active learners) NCTM (Council, 1989), (Ferini-Mundy Martin, 2000). Education is a way to change the fate of a lagging nation into a developed nation. A developed nation begins with advanced education. One way of Learning that is student-centered is to apply different Learning. Differentiated Learning is a form of effort in a series of Learning that pays attention to the needs of students in terms of learning readiness, student learning profiles, interests, and talents. The research design is a qualitative descriptive research design that is directed to analyze the application of differentiation learning by mathematics teachers. Who uses thematic Learning in their schools.